Peningkatan Potensi Sektor Ekonomi Melalui Pemberdayaan Lembaga Masyarakat di Desa Betet Melalui KKN-T`K Universitas Bojonegoro - Reza Anggapratama Anggapratama; Siti Rizqiyatul Munawaroh; Mei Ria Rahayu (Jurnal Pengabdian Kepada Masyarakat Abdi Putra, 2024)
The Bojonegoro University KKN-TK program implemented in Betet Village, Kepohbaru District, Bojonegoro Regency aims to help the village community in overcoming poverty problems in order to achieve prosperity. The preparation of the work program is adjusted to the potential of the village which is focused on empowering community institutions. Based on the results of the village potential analysis, the main work programs were formulated, including (1) Socialization and assistance in financial management and administration of GAPOKTAN; (2) Empowerment of village youth through training in making briquettes from tobacco stem waste; (3) Socialization and training in making liquid organic fertilizer (POC); (4) Empowerment of village women through training in making fried onions. The results of this work program were that GAPOKTAN began to implement good administration and financial management, village youth understood the utilization of tobacco waste, farmers began to apply the use of POC and village women had knowledge about entrepreneurship. By utilizing the potential of the village, this work program can have a sustainable impact.